ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN KARBON MONOKSIDA (CO) PADA PEDAGANG SATE DI JAKARTA PUSAT TAHUN 2022 - Yabsutur Rizka, (2023)
Poor air quality can be harmful for humans. The condition of the area with heavy traffic and food grilling activities can increase carbon monoxide (CO) levels that can risk community. The purpose of this study was to determine CO exposure in the future among satay vendors in Central Jakarta. This study used a cross-sectional design study with an Environmental Health Risk Assessment approach. A total of 33 satay vendors were recurited as samples by using a total sampling technique. CO levels were measured by using CO meter at 10 different spots. The results showed that the average CO concentration was 58,569 mg/m3, the average vendor's body weight was 57,3 kg, the average time exposure was 10,67 hours/day, the average duration of exposure was 2,67 years, and the average frequency of exposure was 343 years/day. Regarding the real-time risk level, RQ ≤ 1 was obtained for all vendors. Regarding the lifetime risk level, RQ > 1 was obtained for 30 vendors, while the rest received RQ ≤ 1 within a period of 30 years. It is concluded the health risks owned by vendors show a lifetime effect. Vendors are advised to rest 8 hours/day and use personal protective equipments such as masks.